2020
DOI: 10.1590/s1678-9946202062030
|View full text |Cite
|
Sign up to set email alerts
|

Importation and early local transmission of COVID-19 in Brazil, 2020

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 9 publications
(6 reference statements)
3
79
0
11
Order By: Relevance
“…This is noteworthy because it has been argued that several introductions are necessary for an outbreak to establish in a new location [ 48 ]. The mean time of the most recent common ancestor of all Brazilian strains analysed in this study was estimated to be from 27 January to 22 February 2020, and range that includes the first COVID-19 confirmed case reported in 21 February 2020 [ 49 ]. These results illustrate that by combining genomic data and available epidemiological information we can generate more reliable phylogenetic inferences.…”
Section: Discussionmentioning
confidence: 99%
“…This is noteworthy because it has been argued that several introductions are necessary for an outbreak to establish in a new location [ 48 ]. The mean time of the most recent common ancestor of all Brazilian strains analysed in this study was estimated to be from 27 January to 22 February 2020, and range that includes the first COVID-19 confirmed case reported in 21 February 2020 [ 49 ]. These results illustrate that by combining genomic data and available epidemiological information we can generate more reliable phylogenetic inferences.…”
Section: Discussionmentioning
confidence: 99%
“…7 Escola Politécnica, universidade de são Paulo, são Paulo, Brazil. 8 Brazilian studies Programme, Latin American Centre, university of Oxford, Oxford, uK. 9 MRC Centre for global Infectious Disease Analysis, J-IDEA, Imperial College London, London, uK.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Previous studies revealed that SARS-CoV-2 epidemics in Australia 9,10 , Belgium 11 , Denmark 12 , France 13 , Iceland 14 , Israel 15 , Netherlands 16 Spain 17 and the United States (US) 1820 , resulted from multiple independent introductions, followed by community dissemination of some viral strains that resulted in the emergence of national (or local) transmission clusters. Early phylogenetic analyses of SARS-CoV-2 complete genomes from the Brazilian states of Minas Gerais 21 , Sao Paulo 22 and Amazonas 23 , revealed multiple independent viral importations and limited local spread during the initial stage of the SARS-CoV-2 epidemic in Brazil. Even so, the SARS-CoV-2 genomes analyzed in those previous studies were mostly recovered from individuals returning from international travel, and thus might not have recovered the genetic diversity of SARS-CoV-2 strains linked to community transmission in Brazil.…”
Section: Introductionmentioning
confidence: 99%